Gas adsorption studies in metal-organic frameworks - Newby, Ruth (2016)
This thesis describes the synthesis of a novel highly stable metal-organic framework, NOTT-300(Cr), as well as the synthesis of three new mixed metal analogues of NOTT-300 using different compositions of aluminium and chromium. These new MOFs were used in gas sorption experiments to investigate potential selectivity and uses for gas stream separations with particular focus on CO2 and C2 hydrocarbons. The gas adsorption properties of NOTT-300(Al) for CO2 and C2 hydrocarbons are also investigated in detail. Chapter 1 – An introduction to MOFs, including their synthesis and various applications along with examples from the literature is discussed. The potential application of MOFs for difficult industrial separations is considered and a brief background on CO2 and climate change is discussed along with the current issues facing carbon capture technologies. The uses of C2 hydrocarbons and their difficult separation are also assessed. Chapter 2 – A novel Cr(III) containing analogue of NOTT-300 has been successfully synthesised (NOTT-300(Cr)) and the structure solved from the PXRD pattern. The gas adsorption properties, with specific focus on CO2 uptake and selectivity, are described and compared with those obtained for NOTT 300(Al). The CO2 adsorption in NOTT-300(Cr) was further probed using ¬in situ¬ gas loaded PXRD studies. Flow experiments were used along with IAST calculations to assess and compare the CO2/CH4 and CO2/N2 selectivity in NOTT-300(Cr) and compared with NOTT-300(Al). Although the CO2 adsorption capacity is higher for NOTT-300(Cr) than for NOTT 300(Al) (10.1 vs. 9.5 mmol g-1 at 273 K and 20 bar), the CO2 selectivity is lower due to an increased adsorption capacity for other gases such as CH4. Chapter 3 – A mixed metal NOTT-300 series containing varying amounts of Al and Cr, i.e. NOTT-300(AlCr2:1), NOTT-300(AlCr1:1) and NOTT 300(AlCr2:3), was synthesised in order to further probe the effect of the metal content on the CO2 adsorption and selectivity of this framework. Each of the materials show high CO2 adsorption capacity, however, there appears to be no specific trend in adsorption properties with respect to metal ratio. The CO2 adsorption and selectivity in NOTT 300(AlCr2:1) was further investigated using dual component adsorption isotherms and in situ gas loaded PXRD and IR studies. The three different OH groups present in the mixed metal materials form interactions of differing strength with the CO2 molecules, explaining the different adsorption properties across the series. The mixed metal series displays higher CO2 adsorption than NOTT-300(Al), but lower CO2 selectivity. When compared to NOTT 300(Cr) the CO2 adsorption of the heterometallic series is lower but the selectivities are comparable. Chapter 4 – The adsorption of C2 hydrocarbons and possible C2 separations and C2/C1 separations are investigated and compared in the NOTT-300 materials described in this thesis. All frameworks display considerably higher adsorption capacity for C2 hydrocarbons vs. CH4. However, the potential for C2 separations was more varied, with NOTT-300(AlCr1:1) showing moderate C2H4/C2H6 selectivity (2.7:1), while the calculated selectivity for NOTT 300(Cr) was negligible (1:1). NOTT-300(Al) was used in breakthrough experiments to assess the separation capability of two different hydrocarbon mixtures (C2H2/C2H4 and C2H4/C2H6).